An assessment of density estimation methods for forest ungulates - Ellis, Amanda Morgan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
The development of conservation and management programs for an animal population relies on a knowledge of the number of individuals in an area. In order to achieve reliable estimates, precise and accurate techniques for estimating population densities are needed. This study compared the use of direct and indirect methods of estimating kudu (Trage/aphus strepsiceras), bush buck (Trage/aphus scriptus), common duiker (Sy/vicapra grimmia), and blue duiker (Philantamba manticala) densities on Shamwari Game Reserve in the Eastern Cape Province, South Africa. These species prefer habitats of dense forest and bush for concealment and are therefore not easily counted in open areas. Herein direct observation counts were compared to indirect sampling via pellet group counts (clearance plots, line transects, variable-width transects, and strip transects). Clearance plots were examined every 2 weeks, while all other methods were conducted seasonally, from August 2002 until August 2003. The strip transect method provided the lowest density estimates (animals per hal ranging from 0.001 for bushbuck to 0.025 for common duiker, while direct observations yielded the highest estimates, ranging from 0.804 for bush buck to 4.692 for kudu. Also, a validation of methods was performed against a known population of kudu during which the DISTANCE method yielded the most accurate results, with an estimated density of 0.261 that was within the actual density of 0.246 to 0.282. In addition, the DISTANCE method was compared to helicopter counts ofkudu and its estimates were found to be approximately 2.6 times greater than the helicopter count results. When the assessment of the methods was made, the cost, manpower and effort requirements, coefficient of variation, and performance against a known population for each method were taken into consideration. Overall, the DISTANCE method performed the best with low cost, minimal manpower and effort requirements, and low coefficient of variation. On Shamwari Game Reserve, the DISTANCE method estimated 0.300 kudu, 0.108 bushbuck, 0.387 common duiker, and 0.028 blue duiker per ha, which, when extrapolated to the total number of animals present within subtropical thicket habitat, estimated 1973 kudu, 710 bush buck, 2545 common duiker, and 184 blue duiker.
Keywords: Wildlife management -- South Africa -- Eastern Cape; Animal populations -- Estimates; Wildlife conservation -- South Africa -- Eastern Cape; Game farms -- South Africa -- Eastern Cape; Ungulates -- South Africa -- Eastern Cape